The Role of Information Technology and Product Innovation on the Competitive Advantage of Companies at Jember East Java - Cendekiawan, Khrisna Agung; Wardhani, Firdha Aprillia (Pascasarjana STIE Miftahul Huda, 2025)
This study aims to analyze the role of information technology and product innovation in creating a competitive advantage for companies in Jember, East Java. Competitive advantage is a critical factor in determining the survival and success of companies in an increasingly competitive market. Using a qualitative research method, this study explores the perspectives of key stakeholders within companies regarding the implementation of information technology and product innovation. In-depth interviews with company leaders, along with secondary data analysis, were employed to gain insights into how these two factors contribute to the company’s strategy. The findings of this study reveal that information technology plays a crucial role in enhancing operational efficiency, internal communication, and facilitating access to global markets. Additionally, product innovation proves to be a key differentiator for companies, enabling them to meet the ever-evolving needs of consumers. The research also highlights that companies successfully integrating both elements are able to build and sustain a competitive advantage. Overall, the findings demonstrate the importance of adapting to new technologies and continuously innovating in order to maintain a company’s competitiveness in the digital era.